Heidegger and Baudrillard on Death, Posthumanity, and the Challenge of Authenticity - Pasco, Marc Oliver D (Archīum Ateneo, 2023)
Using insights from Jean Baudrillard and Martin Heidegger, this work explores the possibility of re-imagining the relationship between death and authenticity in the age of information technologies. It begins by discussing how Baudrillard argues that we have entered the posthuman age where the self identifies itself as data in the hyperreal world of cyberspace. Next, Heidegger’s insights on angst, death, and authenticity, while providing an ontological purview for examining the ontical permutation of being human, will be re-imagined and re-interpreted, and then used as a lens with which to understand how posthuman subjectivity possibly experiences inauthenticity, angst, and mortality in the present context. This posthuman scenario reduces the self into an amalgam of virtual personas that try to conform itself to the demands of the hyperreal. When this happens, the self becomes ontically fractured and its experience of finitude, its call to wholeness is substituted by the appeal of further segmentation and dispersion. It will finally be argued that it is in this very condition that Dasein can once again recover its essential sense of self as the obscenity of cyberspace only heightens Dasein’s sense of anguish as it tries to navigate a place that is both nowhere and everywhere.